Pengaruh Kualitas Produk, Citra Merek, dan Kepercayaan Merek Terhadap Loyalitas Merek Sepeda Motor Merek Honda - Amelia, Meita; Herawati, Sri (REVITALISASI : Jurnal Ilmu Manajemen, 2024)
This research purposely to analysis the impact of product quality, brand image also brand trust towards brand loyalty in Honda motorbike products in the city of Bandung. The research has been tested using multiple regression, descriptive analysis, classical assumption, validity also reliability methods. This instrument were to ultilized as an information assortment device from respondents matured something like 17->31 years who utilizedHonda brand motorbikes. The softwareversion 25 of SPSS was using as the analytical tool to test the data instrument. This research was using secondary data from the Top Brand Index and AISI data for 2022 and 2023, as well as primary data from online questionnaire distribution to 120 respondents. Of the four proposed research hypotheses, the yield this research shown that the variables of brand quality, brand image, also brand trust has a positive impact towards brand loyalty. It was hoping that the yields of this research would be provide benefits for further research also benefits for the Honda Company